Fertility effects of college education: Evidence from the German educational expansion - Daniel A. Kamhöfer; Matthias Westphal (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2019)
Using arguably exogenous variation in college expansions we estimate the effects of college education on female fertility. While college education reduces the probability of becoming a mother, college-educated mothers have more children than mothers without a college education. Lower child-income penalties of college-educated mothers of two relative to mothers without college up to nine years after birth suggest a stronger polarization of college graduate jobs into family-friendly and career-oriented as a potential explanation. We conclude that policies aiming at increasing female educational participation should be counteracted by policies enabling especially college graduates to have both a career and a family.
Keywords: C36; I21; J13; 330; family planning; college education; augmented quantity-quality model